Method for producing a silicon carbide composite ultra-high temperature ceramic coating

CN122916728APending Publication Date: 2026-10-16JIANGXI XINDA HANGKE NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611322413.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对现有Cf/SiC复合材料抗氧化涂层制备工艺设备昂贵、高温加工损伤基体、涂层结合力不足、复杂异形工件难以均匀涂覆、高温抗氧化与自愈合性能差等技术缺陷,本发明提供一种碳化硅复合材料超高温陶瓷涂层的制备方法,依托 PCS/DVB 有机粘结浆料体系搭配低温真空固化工艺,全程无高温加工工序,设备简单、操作门槛低,涂层与基体兼具机械啮合与化学键合双重结合作用,高温服役过程可生成硼硅酸盐玻璃相实现氧化通道自封闭,显著提升Cf/SiC复合材料1200℃高温抗氧化性能

Benefits of technology

[0027] 1. Excellent high-temperature oxidation resistance and self-healing properties: After static air oxidation test at 1200℃ for 30 minutes, the Cf/SiC composite material coated with the coating of this invention has an oxidation weight loss rate of only 0.60% and a matrix strength retention rate of up to 97%. Under high-temperature oxidation environment, the boron powder inside the coating reacts with oxygen and SiC to generate a molten borosilicate glass phase. The glass phase can flow and fill the microcracks and pores inside the coating and matrix, forming a dynamic self-healing oxygen barrier layer, which provides long-term protection against oxidation of the internal carbon fibers.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a preparation method of a silicon carbide composite ultra-high-temperature ceramic coating, and adopts multi-stage sandpaper to polish and roughen a Cf / SiC base and perform ultrasonic cleaning; then, a stable brushable ceramic slurry is prepared by using PCS / DVB as a composite bonding solvent and compounding specific-particle-size SiC and B powder; finally, a protective coating is obtained through long-time room-temperature pre-drying and 120 DEG C low-temperature vacuum segmented curing. The application is free of high-temperature processing procedures in the whole process, is simple in equipment, is low in production cost, is suitable for plane, curved surface and various types of Cf / SiC workpieces, has high interfacial bonding strength due to the double bonding effect of chemical bonding and mechanical engagement of the coating and the base, has a weight loss of only 0.60% in 1200 DEG C high-temperature oxidation test, generates borosilicate glass phase at high temperature to realize crack self-healing, effectively blocks oxygen penetration to protect the internal carbon fiber, solves the defects of expensive traditional CVD and thermal spraying process equipment, high-temperature damage to the base and coating difficulty of special-shaped parts, and is suitable for batch preparation of various types of aerospace vehicle Cf / SiC thermal protection components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic coating technology, specifically to a method for preparing ultra-high temperature ceramic coatings made of silicon carbide composite materials. Background Technology

[0002] Carbon fiber reinforced silicon carbide (Cf / SiC) composites, with their excellent comprehensive properties such as high specific strength, high specific modulus, wear resistance, and resistance to high-temperature ablation, are core candidate materials for thermal protection structures in aerospace vehicles. However, this material has inherent defects: the carbon fibers inside the composite are extremely prone to oxidation at high temperatures; after the matrix is ​​formed, there are a large number of microcracks and penetrating pores on the surface and inside. In a high-temperature oxidizing atmosphere, oxygen can rapidly penetrate into the material through the pores, continuously corroding the carbon fibers, causing a precipitous decline in the mechanical properties of the composite and significantly shortening the service life of the components.

[0003] The mainstream preparation methods for existing Cf / SiC antioxidant protective coatings can be divided into three categories: The first category is chemical vapor deposition (CVD) and physical vapor deposition (PVD), which can prepare dense SiC protective layers, but the purchase and operation costs of the entire set of equipment are high, the deposition process requires a high-temperature vacuum environment, the high-temperature process can damage the carbon fibers inside the substrate, and it is only suitable for simple and regular planar components; The second category is plasma and flame thermal spraying processes, where the coating and the substrate rely only on mechanical interlocking, resulting in low interfacial bonding strength. The high-temperature flame of thermal spraying can cause thermal stress damage to the substrate, making it difficult to achieve uniform full coverage of complex curved surfaces and internal cavity components; The third category is the traditional sol-gel coating process, where the coating porosity is high after the gel system decomposes at high temperatures, resulting in poor oxygen barrier ability and no self-healing protective mechanism at high temperatures.

[0004] The existing processes mentioned above all have drawbacks such as large equipment investment, long preparation cycle, easy damage to Cf / SiC matrix, and poor adaptability to coating irregular parts. The industry urgently needs a method for preparing ultra-high temperature anti-oxidation ceramic coatings that can be operated at room temperature, cured at low temperature, low cost, has high interfacial bonding strength, and is suitable for complex curved surface components. Summary of the Invention

[0005] To address the shortcomings of existing Cf / SiC composite material antioxidant coating preparation processes, such as expensive equipment, high-temperature processing damage to the substrate, insufficient coating adhesion, difficulty in uniform coating of complex irregular workpieces, and poor high-temperature antioxidant and self-healing properties, this invention provides a method for preparing ultra-high temperature ceramic coatings for silicon carbide composite materials. This method utilizes a PCS / DVB organic binder slurry system combined with a low-temperature vacuum curing process, eliminating high-temperature processing steps throughout. The equipment is simple and the operation is easy. The coating and substrate exhibit both mechanical and chemical bonding, and during high-temperature service, a borosilicate glass phase is generated to achieve self-sealing of oxidation channels, significantly improving the high-temperature antioxidant performance of Cf / SiC composite materials at 1200℃.

[0006] To achieve the above objectives, the present invention adopts the following technical solution:

[0007] A method for preparing an ultra-high temperature ceramic coating of silicon carbide composite material includes the following steps:

[0008] S1: Cf / SiC matrix pretreatment: Take the carbon fiber reinforced silicon carbide composite workpiece and successively polish the entire outer surface of the workpiece with 400-grit, 800-grit, and 1200-grit alumina sandpaper. After polishing, immerse the workpiece in anhydrous ethanol for ultrasonic cleaning for 15-20 minutes to remove surface dust, oil, and demolding impurities. Place it in a room temperature ventilated environment to dry completely. Multi-level sandpaper polishing simultaneously cleans and roughens the matrix surface, forming a micron-level uneven microstructure on the matrix surface.

[0009] S2: Preparation of Ultra-High Temperature Ceramic Protective Slurry:

[0010] (1) Preparation of composite adhesive solvent: Polycarbosilane powder and divinylbenzene are mixed at a mass ratio of 1:2.5 to 1:3 and magnetically stirred at room temperature for 2 hours until the polycarbosilane powder is completely dissolved to obtain a homogeneous transparent polycarbosilane / divinylbenzene composite adhesive solvent.

[0011] (2) Composite ceramic solid filler: SiC micro powder with a particle size of 2-5 μm is mixed with elemental boron powder with a particle size of 1-3 μm, and the mass ratio of the two is 7:3-8:2;

[0012] (3) Dispersion preparation of stable slurry: The mixed ceramic solid filler is added to the polycarbosilane / divinylbenzene composite adhesive solvent in batches. The total mass of the solid filler accounts for 35% to 45% of the total mass of the composite adhesive solvent. The mixture is mechanically stirred at room temperature for 3 to 4 hours, and the stirring speed is controlled at 300 to 400 r / min. Ultrasonic dispersion is used simultaneously during the stirring process to eliminate powder agglomeration, so as to obtain a ceramic protective slurry that is free from stratification and precipitation and can be continuously brushed.

[0013] S3: Multi-layer coating: A soft brush and a stainless steel scraper are used to coat the ceramic slurry obtained in S2 evenly on the surface of the Cf / SiC workpiece after S1 pretreatment. The thickness of each coating layer is controlled between 20 and 40 μm. After each coating layer is completed, the workpiece is left to stand for 1.5 hours before the next coating layer is applied. The total number of coating layers is set to 2 to 5 layers.

[0014] S4: Segmented low-temperature vacuum curing:

[0015] (1) Room temperature pre-drying: After the workpiece is coated, it is placed in a dust-free and ventilated environment to dry naturally for 36 to 48 hours to pre-evaporate the free divinylbenzene solvent inside the slurry;

[0016] (2) Vacuum constant temperature curing: The pre-dried workpiece is transferred into a vacuum drying oven, and the vacuum degree inside the oven is maintained at -0.08 to -0.09 MPa. The temperature is increased to 120℃ at a rate of 2℃ / min, and the workpiece is kept at a constant temperature for 10 to 12 hours. After curing, the workpiece is naturally cooled to room temperature in the vacuum drying oven, forming a dense ultra-high temperature ceramic protective coating on the surface of the Cf / SiC workpiece.

[0017] Preferably, in step S2, the SiC micro powder has a particle size of 3 μm, the elemental boron powder has a particle size of 2 μm, the mass ratio of SiC micro powder to elemental boron powder is 7.5:2.5, and the total mass of solid filler accounts for 40% of the total mass of polycarbosilane / divinylbenzene composite binder solvent.

[0018] Preferably, the ambient temperature for the coating process in step S3 is controlled at 20–28°C, the relative humidity of the ambient air is ≤50%, and the construction environment is kept dust-free and free from direct airflow onto the workpiece surface.

[0019] Preferably, in the S4 step of vacuum constant temperature curing stage, before heating to 120°C for constant temperature curing, a gradient heating process of 60°C constant temperature holding for 2 hours is added to slowly remove residual free solvent inside the slurry.

[0020] Preferably, the ultrasonic cleaning power in step S1 is 300W, the ultrasonic cleaning temperature is controlled at room temperature of 22-26℃, and the standard for drying the workpiece after cleaning is that there are no visible ethanol water stains on the surface.

[0021] Preferably, in step S2, the ultrasonic power of the mechanical stirring and ultrasonic dispersion is 200W, and the ultrasonic dispersion is carried out with a 5-minute interval after every 30 minutes of stirring, and the cycle is repeated until the total stirring time reaches 3-4 hours.

[0022] Preferably, for curved or hollowed-out irregular Cf / SiC components, the total number of coating layers is set to 3 to 5 layers, and the thickness of a single coating is controlled to be 20 to 30 μm to reduce the defects of slurry dripping on curved surfaces.

[0023] Preferably, for large-size planar Cf / SiC substrates, the total number of coating layers is set to 2 to 3, and the thickness of a single coating is controlled to be 30 to 40 μm, thereby shortening the overall preparation cycle.

[0024] Preferably, after curing, the ceramic protective coating obtained is exposed to a static air oxidation environment at 1200℃ for 30 minutes, and the workpiece oxidation weight loss rate is ≤0.60%, and the Cf / SiC matrix strength retention rate is ≥97%. During the high-temperature oxidation process, the boron inside the coating reacts with oxygen and silicon carbide to generate a molten borosilicate glass phase, which fills the microcracks inside the coating and the matrix to achieve self-healing and oxidation resistance.

[0025] Preferably, the entire preparation process uses only conventional equipment such as sandpaper, ultrasonic cleaner, mechanical stirrer, ultrasonic dispersion equipment, and vacuum drying oven, without the need for CVD, PVD, or thermal spraying special high-temperature deposition spraying equipment; all coating and pre-drying processes are completed in a normal temperature and pressure environment, with a maximum heat treatment temperature of only 120℃, which will not damage the original mechanical properties of the carbon fibers inside the Cf / SiC composite material.

[0026] Compared with the prior art, the beneficial effects of the present invention are:

[0027] 1. Excellent high-temperature oxidation resistance and self-healing properties: After static air oxidation test at 1200℃ for 30 minutes, the Cf / SiC composite material coated with the coating of this invention has an oxidation weight loss rate of only 0.60% and a matrix strength retention rate of up to 97%. Under high-temperature oxidation environment, the boron powder inside the coating reacts with oxygen and SiC to generate a molten borosilicate glass phase. The glass phase can flow and fill the microcracks and pores inside the coating and matrix, forming a dynamic self-healing oxygen barrier layer, which provides long-term protection against oxidation of the internal carbon fibers.

[0028] 2. High bonding strength between coating and substrate interface: The substrate is roughened by multi-level sandpaper to form a micro-uneven structure. After the polycarbosilane organic component in the slurry is cured, it forms a chemical bond with the Si element on the surface of the Cf / SiC substrate. At the same time, the powder filler is embedded in the micro-grooves of the substrate to form a mechanical interlocking dual bonding mechanism. The coating does not peel or flake. The maximum temperature during the curing process is only 120℃, which will not cause thermal damage to the carbon fibers inside Cf / SiC. The original mechanical properties of the substrate are not reduced.

[0029] 3. Simple process and extremely low production cost: No high-cost special deposition and spraying equipment such as CVD, PVD, and thermal spraying are required. Only a stirrer, ultrasonic cleaner, and ordinary vacuum drying oven are needed to complete the entire preparation process. All coating and pre-drying processes are carried out at room temperature and pressure, resulting in low energy consumption and equipment purchase and maintenance costs that are far lower than those of traditional high-temperature coating processes.

[0030] 4. Strong adaptability and versatility for workpieces: The coating process is not limited by the shape of the component and can uniformly cover flat surfaces, large curvature curved surfaces, hollowed-out and thin-walled irregular aerospace thermal protection components. Large-area plates can be coated in batches at one time, and it has high adaptability to large-scale production.

[0031] 5. Dense and intact coating: The segmented drying and gradient low-temperature curing process can gradually remove the slurry solvent, avoid defects such as bubbles, pinholes and cracks inside the coating. After curing, the coating is dense and continuous, which can completely seal the original micropores of the Cf / SiC matrix and block the oxygen diffusion channels. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0033] Example 1

[0034] The coating preparation of flat Cf / SiC thermal insulation material is carried out on a flat Cf / SiC thermal insulation material for aerospace engines. The material surface has slight processing scratches and is used for short-term cyclic oxidation at 1200℃.

[0035] S1: Substrate Pretreatment: The entire surface of the substrate is sanded sequentially using 400-grit, 800-grit, and 1200-grit alumina sandpaper to remove scratches and demolding residue. After sanding, the substrate is ultrasonically cleaned with anhydrous ethanol for 18 minutes at a power of 300W, and then air-dried at room temperature. The multi-stage sanding creates a micro-textured structure on the substrate surface, improving coating adhesion.

[0036] S2: Slurry preparation: Polycarbosilane powder and divinylbenzene are mixed and stirred for 2 hours at a mass ratio of 1:2.8 until completely dissolved; 3μm SiC micro powder and 2μm boron powder are selected, with a mass ratio of 7.5:2.5, and the solid filler accounts for 40% of the total mass of the binder solvent; the filler is added to the solvent in batches, and mechanically stirred at 350r / min for 3.5 hours. After stirring for 30 minutes, ultrasonic dispersion at 200W is performed for 5 minutes to obtain a uniform slurry without sedimentation.

[0037] S3: Brush application: The ambient temperature is 24℃ and the humidity is 42%. A brush and scraper are used for application. The thickness of each coat is 30μm. Each coat is applied 1.5 hours apart. A total of 3 coats are applied. There are no drips or missed areas on the board surface.

[0038] S4: Low temperature curing: After application, pre-dry at room temperature and ventilation for 42 hours; place in a vacuum drying oven with a vacuum degree of -0.085MPa, first keep at 60℃ for 2 hours to remove residual solvent, then raise the temperature to 120℃ at 2℃ / min and keep it at a constant temperature for 11 hours, then cool to room temperature with the oven.

[0039] Performance testing: After 30 minutes of air oxidation at 1200℃, the sample lost 0.58% of its weight and retained 97.2% of the matrix strength. The coating remained intact without cracking or peeling, and the interface bond remained stable after multiple thermal shocks.

[0040] Example 2

[0041] The coating preparation for the leading edge component of the arc-shaped Cf / SiC aircraft is carried out on the arc-shaped Cf / SiC part of the aircraft. The surface has large undulations, and traditional deposition processes are difficult to completely cover it. It is suitable for short-term high-temperature oxidation conditions.

[0042] S1: Substrate pretreatment: Grind the arc surfaces, edges and thin-walled areas of the component step by step to remove the forming burrs; ultrasonically clean with anhydrous ethanol at room temperature for 15 minutes to thoroughly remove dust from the gaps in the curved surface, and then ventilate and dry.

[0043] S2: Slurry preparation: Polycarbosilane powder and divinylbenzene are stirred and dissolved in a mass ratio of 1:2.5; 2μm SiC and 1μm boron powder are compounded in a ratio of 7:3, with the filler accounting for 35% of the solvent; stir at 300r / min for 3h, and then disperse intermittently by ultrasonication to obtain a low-viscosity slurry to avoid sag when brushing on curved surfaces.

[0044] S3: Coating and forming: Ambient temperature 20℃, humidity 48%, use a small round brush to apply a thin coat, with a single coat thickness of 20μm. Apply a second coat after an interval of 1.5 hours, for a total of 2 coats, to ensure uniform coating thickness on all parts of the curved surface.

[0045] S4: Low temperature curing: The workpiece is placed in a dustproof and static drying state for 36 hours; vacuum degree -0.08MPa, directly heated to 120℃ and cured for 10 hours, then cooled with the furnace.

[0046] Performance testing: Weight loss of 0.62% after 30 minutes of oxidation at 1200℃, with 96.8% strength retention; the curved coating is continuous and intact, and the cracks at high temperatures generate a glassy phase to achieve self-healing.

[0047] Example 3

[0048] Preparation of Cf / SiC coating for large-size aerospace cabins: For large-size cabin exterior panels that are subjected to alternating high-temperature thermal shock for a long time, a thicker protective coating is required.

[0049] S1: Substrate pretreatment: Sand both sides of the board with grade 3 sandpaper to eliminate surface pits; clean with anhydrous ethanol in a large-capacity ultrasonic cleaning tank for 20 minutes to fully remove sanding dust from a large area, and then lay flat to air dry completely.

[0050] S2: Slurry preparation: Polycarbosilane powder and divinylbenzene are mixed and dissolved in a 1:3 ratio; 5μm SiC and 3μm boron powder are mixed in an 8:2 ratio, with the filler accounting for 45% of the binder solvent; stir at 400r / min for 4h, and intermittently use ultrasonic to break up powder agglomerates. The slurry has a high solid content and a larger thickness for a single coat.

[0051] S3: Brush application: Ambient temperature 26℃, humidity 45%, use a wide brush and scraper for application, single layer thickness 40μm, each layer is spaced 1.5h apart, a total of 5 layers are applied, relying on multi-layer superposition to increase the total coating thickness.

[0052] S4: Low temperature curing: The board is left to dry statically for 48 hours; vacuum drying oven with a vacuum degree of -0.09MPa, heat at 60℃ for 2 hours, then heat to 120℃ for 12 hours and cure naturally.

[0053] Performance testing: The coating did not peel off after 50 cycles of thermal shock; the weight loss was only 0.56% after 30 minutes of oxidation at 1200℃, and sufficient borosilicate glass phase was generated at high temperature to continuously fill the micro-cracks caused by cyclic stress and effectively block oxygen.

[0054] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.

Claims

1. A method for preparing an ultra-high temperature ceramic coating of silicon carbide composite material, characterized in that, Includes the following steps: S1: Cf / SiC matrix pretreatment: Take the carbon fiber reinforced silicon carbide composite workpiece and successively polish the entire outer surface of the workpiece with 400-grit, 800-grit, and 1200-grit alumina sandpaper. After polishing, immerse the workpiece in anhydrous ethanol for ultrasonic cleaning for 15-20 minutes to remove surface dust, oil, and demolding impurities. Place it in a room temperature ventilated environment to dry completely. Multi-level sandpaper polishing simultaneously cleans and roughens the matrix surface, forming a micron-level uneven microstructure on the matrix surface. S2: Preparation of Ultra-High Temperature Ceramic Protective Slurry: (1) Preparation of composite adhesive solvent: Polycarbosilane powder and divinylbenzene are mixed at a mass ratio of 1:2.5 to 1:3 and magnetically stirred at room temperature for 2 hours until the polycarbosilane powder is completely dissolved to obtain a homogeneous transparent polycarbosilane / divinylbenzene composite adhesive solvent. (2) Composite ceramic solid filler: SiC micro powder with a particle size of 2-5 μm is mixed with elemental boron powder with a particle size of 1-3 μm, and the mass ratio of the two is 7:3-8:2; (3) Dispersion preparation of stable slurry: The mixed ceramic solid filler is added to the polycarbosilane / divinylbenzene composite adhesive solvent in batches. The total mass of the solid filler accounts for 35% to 45% of the total mass of the composite adhesive solvent. The mixture is mechanically stirred at room temperature for 3 to 4 hours, and the stirring speed is controlled at 300 to 400 r / min. Ultrasonic dispersion is used simultaneously during the stirring process to eliminate powder agglomeration, so as to obtain a ceramic protective slurry that is free from stratification and precipitation and can be continuously brushed. S3: Multi-layer coating: A soft brush and a stainless steel scraper are used to coat the ceramic slurry obtained in S2 evenly on the surface of the Cf / SiC workpiece after S1 pretreatment. The thickness of each coating layer is controlled between 20 and 40 μm. After each coating layer is completed, the workpiece is left to stand for 1.5 hours before the next coating layer is applied. The total number of coating layers is set to 2 to 5 layers. S4: Segmented low-temperature vacuum curing: (1) Room temperature pre-drying: After the workpiece is coated, it is placed in a dust-free and ventilated environment to dry naturally for 36 to 48 hours to pre-evaporate the free divinylbenzene solvent inside the slurry; (2) Vacuum constant temperature curing: The pre-dried workpiece is transferred into a vacuum drying oven, and the vacuum degree inside the oven is maintained at -0.08 to -0.09 MPa. The temperature is increased to 120℃ at a rate of 2℃ / min, and the workpiece is kept at a constant temperature for 10 to 12 hours. After curing, the workpiece is naturally cooled to room temperature in the vacuum drying oven, forming a dense ultra-high temperature ceramic protective coating on the surface of the Cf / SiC workpiece.

2. The method for preparing ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, In step S2, the SiC micro powder has a particle size of 3 μm, the elemental boron powder has a particle size of 2 μm, the mass ratio of SiC micro powder to elemental boron powder is 7.5:2.5, and the total mass of solid filler accounts for 40% of the total mass of polycarbosilane / divinylbenzene composite binder solvent.

3. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, The ambient temperature for the coating process in step S3 is controlled at 20–28°C, the relative humidity of the ambient air is ≤50%, and the construction environment is kept dust-free and free from direct airflow onto the workpiece surface.

4. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, In the S4 step, before the vacuum constant temperature curing stage, a gradient heating process of 60°C constant temperature holding for 2 hours is added before the temperature is raised to 120°C for constant temperature curing, in order to slowly remove the residual free solvent inside the slurry.

5. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, The ultrasonic cleaning power in step S1 is 300W, and the ultrasonic cleaning temperature is controlled at room temperature of 22-26℃. After cleaning, the standard for drying the workpiece is that there are no visible ethanol water stains on the surface.

6. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, The ultrasonic power of the mechanical stirring and ultrasonic dispersion in step S2 is 200W. The ultrasonic dispersion is carried out with a 5-minute interval after every 30 minutes of stirring, and the cycle is repeated until the total stirring time reaches 3-4 hours.

7. The method for preparing ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, For curved and hollowed-out irregular Cf / SiC components, the total number of coating layers is set to 3 to 5, and the thickness of a single coating is controlled to 20 to 30 μm to reduce the defects of slurry dripping on curved surfaces.

8. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, For large-size planar Cf / SiC substrates, the total number of coating layers is set to 2 to 3, and the thickness of a single coating is controlled to 30 to 40 μm, thus shortening the overall preparation cycle.

9. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, After curing, the resulting ceramic protective coating was exposed to static air oxidation at 1200℃ for 30 minutes. The oxidation weight loss rate of the workpiece was ≤0.60%, and the strength retention rate of the Cf / SiC matrix was ≥97%. During the high-temperature oxidation process, the boron in the coating reacts with oxygen and silicon carbide to generate a molten borosilicate glass phase, which fills the microcracks in the coating and the matrix to achieve self-healing and oxidation resistance.

10. The method for preparing the ultra-high temperature ceramic coating of silicon carbide composite material according to claim 1, characterized in that, The entire preparation process uses only conventional equipment such as sandpaper, ultrasonic cleaner, mechanical stirrer, ultrasonic dispersion equipment, and vacuum drying oven, without the need for CVD, PVD, or thermal spraying special high-temperature deposition spraying equipment; all coating and pre-drying processes are completed in a normal temperature and pressure environment, with a maximum heat treatment temperature of only 120℃, which will not damage the original mechanical properties of the carbon fibers inside the Cf / SiC composite material.